The social – market convergence in a renewable energy social enterprise. (10th October 2020) - Sengupta, Subhanjan; Sahay, Arunaditya; Hisrich, Robert D.
Abstract: The paper examines how the market and social logics which are supposedly counter to each other, converge into one rather than being two distinctive sets of actions, in the actions of a renewable energy social enterprise in an emerging economy context. To provide a foundation, the research draws upon literature on renewable energy, social entrepreneurship, market orientation, and social value creation. A qualitative in-depth case study research design with inductive theory-building approach for grounded theory development was conducted with two socially and environmentally inclusive renewable energy social enterprises in rural India. This resulted in a novel framework on a converging process comprising of: (a) Involved Searching, (b) Dialogic Localizing, and (c) Engaged Implementing. First, there is 'involved searching', where insights are generated through involved interactions for searching problematized contextual realities. Then, there is 'dialogic localizing', where insights are shared and acted upon through dialogically inclusive and localized solving. Finally, there is 'engaged implementing', where solutions are implemented through honest convincing and engaging mutuality. The findings make a novel contribution towards: (a) Going beyond the duality perspective and revealing social entrepreneurship as a phenomenon where the social and the market converge as an articulated whole, (b) Advancing hybrid organizing as a converging action with trappings of social value creation and market orientation, and (c) Revealing the potential of renewable energy social enterprises in blending the social and the market while working towards a sustainable environment. Highlights: Explores the social–market enactment in what a renewable energy social enterprise does. Reveals the enactment as a convergence of the social and the market as a whole. Generates a grounded framework on the actions constituting this convergence. Offers an approach for research and practice to go beyond a social vs. market debate.